How Do Internal and External CSR Affect Employees' Organizational Identification? A Perspective from the Group Engagement Model - Hameed, Imran; Riaz, Zahid; Arain, Ghulam A.; Farooq, Omer (Frontiers in Psychology, 2016)
The literature examines the impact of firms’ corporate social responsibility (CSR) activities on employees’ organizational identification without considering that such activities tend to have different targets. This study explores how perceived external CSR (efforts directed towards external stakeholders) and perceived internal CSR (efforts directed towards employees) activities influence employees’ organizational identification. In so doing, it examines the alternative underlying mechanisms through which perceived external and internal CSR activities build employees’ identification. Applying the taxonomy prescribed by the group engagement model, the study argues that the effects of perceived external and internal CSR flow through two competing mechanisms: perceived external prestige and perceived internal respect, respectively. Further, it is suggested that calling orientation (how employees see their work contributions) moderates the effects induced by these alternative forms of CSR. The model draws on survey data collected from a sample of 414 employees across five large multinationals in Pakistan. The results obtained using structural equation modeling support these hypotheses, reinforcing the notion that internal and external CSR operate through different mediating mechanisms and more interestingly employees’ calling orientation moderates these relationships to a significant degree. Theoretical contributions and practical implications of results are discussed in detail.